2022
DOI: 10.3390/nu14204370
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Complementary Feeding Indicators: A Secondary Analysis of Thailand Multiple Indicators Cluster Survey 2019

Abstract: Child complementary feeding (CF) practices meet dietary recommendations more often among educated, high-income groups. Much of the evidence for this association addresses inadequate CF for addressing child undernutrition. However, in many countries, including Thailand, child malnutrition assessments must now address under- and over-nutrition. More comprehensive data is needed to understand this complex situation. This study uses data from the Thailand Multiple Indicators Survey 2019, to identify the determinan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…The common food groups of complementary foods in this study found that the Thai mothers first gave to their infants after 6 months of age were grain (rice congee) mixed with vitamin A-rich fruits or vegetables (pumpkin, carrots), which could explain the high vitamin A intake in Thai infants. This is similar to the findings of the previous by mentioned studies from Thailand 14,23 . Mashed banana was also the favorite fruit the Thai mothers gave their infants after the age of 6 months.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The common food groups of complementary foods in this study found that the Thai mothers first gave to their infants after 6 months of age were grain (rice congee) mixed with vitamin A-rich fruits or vegetables (pumpkin, carrots), which could explain the high vitamin A intake in Thai infants. This is similar to the findings of the previous by mentioned studies from Thailand 14,23 . Mashed banana was also the favorite fruit the Thai mothers gave their infants after the age of 6 months.…”
Section: Discussionsupporting
confidence: 92%
“…Also, the MPA of the infants confirmed that the infants that were fed with <4 food groups daily had a very low average MPA: 0.2-0.3, while infants who were fed with >4 food groups had a high average MPA: 0.7-0.9. In this study, complementary feeding was introduced at the ages of 6-7 months, which was a later age than in a national study of 2019, and a study from Pathum Thani in which both found that complementary feedings were introduced at the ages of 4-5 months 14,23 . The common food groups of complementary foods in this study found that the Thai mothers first gave to their infants after 6 months of age were grain (rice congee) mixed with vitamin A-rich fruits or vegetables (pumpkin, carrots), which could explain the high vitamin A intake in Thai infants.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The impact of residential environments on dietary practices and diversity in infants and young children has been extensively studied, yielding varied results. A recent study in Thailand [ 14 ], drawing on secondary data from the 2019 Thailand Multiple Indicators Cluster Survey [ 15 ], found no notable correlation between living in rural or urban areas and DD. However, when considering the minimum acceptable diet, a composite measure encompassing both dietary variety and meal frequency [ 16 ], analysis across multiple countries in South Asia including Afghanistan, Bangladesh, India, Maldives, Nepal, and Pakistan revealed a higher percentage of urban children (15.6%) meeting the standard compared to their rural counterparts (11.8%) [ 17 ].…”
Section: Introductionmentioning
confidence: 99%